Adverse selection and supply‐side factors in the enrollment in community‐based health insurance in Northwest Ethiopia: A mixed methodology. (20th May 2018) - Atafu, Asmamaw; Kwon, Soonman
Summary: Background: Since 2010, the Ethiopian government introduced different measures to implement community‐based health insurance (CBHI) schemes to improve access to health service and reduce the catastrophic effect of health care costs. Objectives: The aim of this study was to examine the determinants of enrollment in CBHI in Northwest Ethiopia. Methods: In this study, we utilized a mix of quantitative (multivariate logistic regression applied to population survey linked with health facility survey) and qualitative (focus group discussion and in‐depth interview) methods to better understand the factors that affect CBHI enrollment. Results: The study revealed important factors, such as household, informal association, and health facility, as barriers to CBHI enrollment. Age and educational status, self‐rated health status, perceived quality of health services, knowledge, and information (awareness) about CBHI were among the characteristics of individual household head, affecting enrollment. Household size and participation in an informal association, such as local credit associations, were also positively associated with CBHI enrollment. Additionally, health facility factors like unavailability of laboratory tests were the main factor that hinders CBHI enrollment. Conclusions: This study showed a possibility of adverse selection in CBHI enrollment. Additionally, perceived quality of health services, knowledge, and information (awareness) are positively associated with CBHI enrollment. Therefore, policy interventions to mitigate adverse selection as well as provision of social marketing activities are crucial to increase enrollment in CBHI. Furthermore, policy interventions that enhance the capacity of health facilities and schemes to provide the promised services are necessary.